The impact of Foreign Direct Investment from the European Union to Singapore - Hrazdíra, Adam; Klosová, Anna, 1942-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The goal of this dissertation is to investigate the impact of FDI flows from the European countries to Singapore. The analysis focuses on the period between 1995 and 2013. The work begins with the review of the relevant literature. The most important findings about spillover, spinoff effects, and the main FDI determinants are summarized in tables. The empirical part reveals the trends of FDI in Singapore with an emphasis on the influence of FDI from European countries. The work contains two main research questions: Does FDI from European countries have a positive impact on GDP growth in Singapore? Is it possible to identify the main determinants that attract FDI in Singapore? Time series analyses and panel analyses are used in the dissertation. Among the most valuable results belong the confirmation of a positive impact of FDI from Europe on GDP growth and the identification of some of the main positive determinants for attracting FDI in Singapore.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses